Apiculture productive development as a source socio-sconomic improvement vereda corralejas – Sotará Cauca - Velasco- Hurtado, Dora Silvana; Barreda- Ramírez, Concepción; Ordoñez- Ortega, Danny Astrid (Universidad Francisco de Paula Santander, 2019)
The general objective of this research was to determine the impact of beekeeping production development on the socioeconomic improvement of beekeepers, and to design strategies and action plans to encourage associativity and participation in short marketing circuits. The diagnosis is presented using a mixed approach methodology, applying quantitative and qualitative analysis and an exploratory, descriptive and observational approach. The methodology used included consultation with the inhabitants and beekeepers of Corralejas. The instruments used were survey and interview. The population consisted of 374 inhabitants, a sample of 190 people to whom the survey was applied and later, the beekeepers were interviewed, and field notes and photographic records were taken. According to the information analyzed, the incidence and impact of beekeeping in the economic, social and environmental sector is evident, considering that it contributes to improving the quality of life of those who work in this subsector. On the other hand, the benefits of beekeeping are ratified and it is determined as an economic activity that generates additional income, strengthening the peasant, family and community economy, the synergies between actors in the territory, and the dynamization of productive diversification.